2011
DOI: 10.1371/journal.pone.0022769
|View full text |Cite
|
Sign up to set email alerts
|

PIK3CA Mutations Frequently Coexist with RAS and BRAF Mutations in Patients with Advanced Cancers

Abstract: BackgroundOncogenic mutations of PIK3CA, RAS (KRAS, NRAS), and BRAF have been identified in various malignancies, and activate the PI3K/AKT/mTOR and RAS/RAF/MEK pathways, respectively. Both pathways are critical drivers of tumorigenesis.MethodsTumor tissues from 504 patients with diverse cancers referred to the Clinical Center for Targeted Therapy at MD Anderson Cancer Center starting in October 2008 were analyzed for PIK3CA, RAS (KRAS, NRAS), and BRAF mutations using polymerase chain reaction-based DNA sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
113
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(131 citation statements)
references
References 47 publications
14
113
1
1
Order By: Relevance
“…Concomitant BRAF and RAS mutations may allow simultaneous activation of the MAPK and PI3K/Akt signaling pathways in cancer cells, providing a growth advantage (47,48). Long-term follow-up revealed that patients with concomitant mutations had a poorer response to treatment and reduced disease-free survival times (49), indicating that activation of the two genes may have a synergistic effect on disease progression (50).…”
Section: Hras Status N (%) -----------------------------------------mentioning
confidence: 99%
“…Concomitant BRAF and RAS mutations may allow simultaneous activation of the MAPK and PI3K/Akt signaling pathways in cancer cells, providing a growth advantage (47,48). Long-term follow-up revealed that patients with concomitant mutations had a poorer response to treatment and reduced disease-free survival times (49), indicating that activation of the two genes may have a synergistic effect on disease progression (50).…”
Section: Hras Status N (%) -----------------------------------------mentioning
confidence: 99%
“…Another perspective for this issue derives from studies showing that, in colorectal cancer patients, aberrations in the KRAS/BRAF axis often coexist with aberrations in the PI3K/AKT/mTOR axis (83)(84)(85), with each being a resistance pathway for the other (86,87). These co-mutations occur in other cancers as well, but not as frequently.…”
Section: Role Of the Pi3k/akt/mtor Axismentioning
confidence: 99%
“…Loss of PTEN expression, assessed by immunohistochemistry, is found in as many as 40% of colorectal cancer tumors (4)(5)(6). Importantly, the RAS/RAF/MEK and PI3K/AKT/ mTOR pathways also interact extensively: (i) each shows activation of upstream receptor tyrosine kinases; (ii) mutations in KRAS or BRAF and PIK3CA coexist in a significant percentage of colorectal tumors; and (iii) complex networks allow compensatory parallel signaling when one or the other pathway is inhibited (7).…”
Section: Introductionmentioning
confidence: 99%